2008
DOI: 10.1271/bbb.70302
|View full text |Cite
|
Sign up to set email alerts
|

Gene Cloning and Biochemical Characterization of the BMP-2 ofPinctada fucata

Abstract: The bone morphogenetic proteins (BMPs) constitute a subfamily of the transforming growth factor type beta (TGF-) supergene family. BMP-2 plays an important role not only in osteoblast differentiation but also in pattern formation during development. To determine the function of BMP-2 in Pinctada fucata development and hard tissue formation, we isolated a BMP-2 genomic DNA clone and the BMP-2 cDNA. The deduced BMP-2 sequence consisted of 447 amino acids. The BMP-2 gene was composed of three exons. The C-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…The down-regulated genes in the subnetwork, namely, WNT5A , FOXF2 and RARB , play important roles in the differentiation of embryonic stem cells [57], [58], [59]. It is interesting to observe that these genes have GLI binding sites in their promoter region or cis-regulatory domains, which suggests that GLI1 and ZIC3 could potentially regulate their expression in ES cells [60], [61]. Also, GLI proteins participate in regulation of Hedgehog signaling, of which RARB and FOXF2 are members, and GLI is also known to regulate the members of WNT family [62].…”
Section: Resultsmentioning
confidence: 99%
“…The down-regulated genes in the subnetwork, namely, WNT5A , FOXF2 and RARB , play important roles in the differentiation of embryonic stem cells [57], [58], [59]. It is interesting to observe that these genes have GLI binding sites in their promoter region or cis-regulatory domains, which suggests that GLI1 and ZIC3 could potentially regulate their expression in ES cells [60], [61]. Also, GLI proteins participate in regulation of Hedgehog signaling, of which RARB and FOXF2 are members, and GLI is also known to regulate the members of WNT family [62].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally Dennler et al reported that GLI2 and GLI1 could be induced through a SMAD-mediated mechanism [36]. The TGF-β superfamily genes BMP-2, 4 , & 7 all have GLI-responsive elements in their promoters[37][39]. Lin et al found a SHH-responsive element in the 5′-upstream promoter region of TGF-β2 [40].…”
Section: Discussionmentioning
confidence: 99%
“…The construction of the genomic library and the cloning of genomic clones of nacrein were performed essentially as described previously (Miyashita et al 2008), with the following modifications. Hybridization was performed at 50 °C, and the filters were washed twice with 0.1× SSC (standard saline citrate), 1 % SDS, for 10 min at room temperature, before being washed twice with 0.1× SSC, 1 % SDS, for 20 min at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The membrane was hybridized with a nacrein cDNA of approximately 2.3 kbp or human β-actin cDNA and labeled with digoxigenin-dUTP by the random primer method (Boehringer Mannheim). Hybridization and detection were performed as described previously (Miyashita et al 2008). …”
Section: Methodsmentioning
confidence: 99%